Are generalist batterers different from generally extra-family violent men? A study among imprisoned male violent offenders - Fernández Suárez, Asunción (European journal of psychology applied to legal context, 2018)
Research on male batterers has found that in some cases of severe intimate partner violence (IPV) against women, male aggressors were also generally violent beyond the family realm. These findings have been used by researchers to illustrate the common etiology of both general and IPV. Using data from imprisoned male violent offenders, we analyzed the individual, family, and community characteristics of two groups of violent offenders: generalist batterers (GB) and generally extra-family violent men (GEVM). GB offenders had a judicial sentence on IPV-related offenses (gender violence according to the Spanish legislation), while GEVM offenders did not have any IPV-related judicial sentence. The sample includes 153 imprisoned male violent offenders of the Penitentiary Center of Villabona (Asturias, Spain). Sociodemographic measures, and criminal and justice official records of participants are available. Two groups of participants (GB and GEVM) distinction was done based on official records. Multivariate analyses of covariance (MANCOVA) was carried out to study differences between each group of participants in self-reported measures of personal, family, and community context variables. MANCOVA showed no statistical differences among the individual, family, and community characteristics of these two groups, giving empirical support to the theoretical view that general violence and IPV might share a common etiology. These results are discussed in light of the debate about the potentially common etiology of these two types of violence